2005
DOI: 10.1016/j.febslet.2005.09.022
|View full text |Cite
|
Sign up to set email alerts
|

The adiponectin paralog CORS‐26 has anti‐inflammatory properties and is produced by human monocytic cells

Abstract: The adiponectin paralog CORS-26 (collagenous repeat-containing sequence of 26 kDa protein) is a member of the C1q/TNF-a molecular superfamily. CORS-26 is a secreted protein and baculovirus-produced CORS-26 released in the supernatant of insect cells forms stable trimers. Adiponectin exerts anti-inflammatory effects in LPS-treated monocytic cells and CORS-26 also reduces IL-6 and TNF-a secretion but does not increase IL-10. Suppression of NFjB signalling may explain the anti-inflammatory actions of CORS-26. Fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
75
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 16 publications
3
75
2
Order By: Relevance
“…Previous in vitro studies have shown that CTRP3 (also known as CORS26/cartducin) (18) stimulates chondrogenic precursor cell proliferation (19), promotes angiogenesis (20), and is overexpressed in the osteosarcoma cell line (21). In primary monocytes derived from healthy but not type 2 diabetic humans, recombinant human CTRP3 reduces proinflammatory cytokine IL-6 and TNF-␣ secretion in response to lipopolysaccharide stimulation, suggesting an anti-inflammatory role (22). Beyond these in vitro studies, the biological relevance and function of CTRP3 in vivo remain unknown.…”
mentioning
confidence: 99%
“…Previous in vitro studies have shown that CTRP3 (also known as CORS26/cartducin) (18) stimulates chondrogenic precursor cell proliferation (19), promotes angiogenesis (20), and is overexpressed in the osteosarcoma cell line (21). In primary monocytes derived from healthy but not type 2 diabetic humans, recombinant human CTRP3 reduces proinflammatory cytokine IL-6 and TNF-␣ secretion in response to lipopolysaccharide stimulation, suggesting an anti-inflammatory role (22). Beyond these in vitro studies, the biological relevance and function of CTRP3 in vivo remain unknown.…”
mentioning
confidence: 99%
“…In this context, it is important to note that human CORS-26 mRNA is up-regulated in osteosarcoma cells. These data also indicate a role for CORS-26 in the context of mesenchymal tissue development and in the pathogenesis of bone and skeletal diseases 6 . Akiyama et al 7 have reported that stimulation of osteosarcoma cells by CORS-26 promotes tumor cell growth but not migration in vitro.…”
Section: Cors-26 In the Regulation Of Osteosarcoma Cellsmentioning
confidence: 84%
“…Whereas adiponectin is exclusively expressed by adipocytes, CORS-26 mRNA is also detected in cartilage, kidney, colon, small intestine, placenta, lung, spleen, fibroblasts, human monocytic and dendritic cells 5,6 . In addition, strong CORS-26 mRNA expression has been found in osteosarcoma, chondroblastoma and giant cell tumors 2,3,6 . …”
Section: Cors-26 Expressionmentioning
confidence: 99%
See 2 more Smart Citations